Semantic Basis of Lexical Expressiveness (Linguostylistic Studies, 2016)
In the article the two main types of lexical expressiveness are considered: inherent (denotative-connotative, connotative-denotative, connotative) and adherent (functional-semantic, functional-stylistic). The emphasisis is laid on the semantic basis of lexical expressiveness. The author distinguishes between language (semantic) expressiveness and speech (functional) expressiveness, and offers division of expressive lexical units into four basic classes: 1) expressive units with usual primary meaning (most frequently used); 2) expressive units with usual derivative meaning; 3) expressives with occasional contextual meaning; 4) words with stylistically stipulated expressive colouring. The article provides rich illustrative material to approve the role and coorilation of denotation and connotation in the structure of the expressive word lexical meaning.  The article concludes that  model of semantic structure of expressive words lexical meaning  is represented by inherent expressive meaning, expressive colouring and expressive potential. Key words: lexical expressiveness, expressivity gerente, adherent expressiveness, dentity macro component, connotative macro component,  macro component of a figurative expression. References